P155 The microRNA 34 family and its clinical significance in ovarian cancer. (1st November 2019) - Welponer, H; Tsibulak, I; Wieser, V; Degasper, C; Shivalingaiah, G; Wenzel, S; Sprung, S; Marth, C; Fiegl, H; Zeimet, AG
Abstract : Introduction/Background: The tumor suppressor miR-34 family is transcriptionally induced by p53. Clinical significance of the various miR-34 family members has not been studied in ovarian cancer. Methodology: In 228 ovarian cancers and in 19 non-neoplastic fallopian tube samples we analysed miR-34a/b/c expression in relation to clinicopathological characteristics and clinical outcome. Results: We found significantly lower levels of miR-34a/b/c in ovarian cancers as compared to control-tissues ( P =0.002, P <0.001, P <0.001, respectively). Expression of miR-34b/c revealed an inverse correlation with BRCA1/2 mRNA-expression (BRCA1: miR34b/c P =0.002 each; BRCA2: miR-34b/c P<0.001 each), the same was true for miR-34a and BRCA2 mRNA-expression ( P <0.001). The miR-34 family expression was found to be significantly lower in type 2 in comparison to type 1 cancers (P<0.001) and in TP53 -mutated compared with TP53 -wild-type ovarian cancers ( P <0.001, P =0.002, P =0.004, respectively). When low grade serous ovarian cancers were compared with high grade serous cancers the respective miR-34a/b/c expression was 2.6-, 40.8- and 32.3-fold higher. The expression of each of the miR-34 family members was revealed to be of independent prognostic relevance regarding progression free survival (miR-34a: HR 0.6, P =0.033; miR-34b: HR 0.2, P =0.001 and miR-34c: HR 0.3, P =0.002, respectively). For overall survival independency of the prognostic value was confined to miR-34b (HR 0.4, P =0.016) and miR-34c (HR 0.6, P =0.049). Conclusion: Our findings suggest that downregulation of miR-34 family is a crucial part in ovarian cancer development. Low miR-34 levels are linked to a worse overall survival and progression free survival and may indicate a more aggressive disease. Disclosure: Nothing to disclose.